652 Fate of The Contralateral Limb Following Major Lower Limb Amputation in Patients with Peripheral Arterial Disease And/Or Diabetes: Case Series from Two Regional Vascular Centres. (12th October 2021) - Siddle, H; Bonner, R; Leighton, P; McGinnis, E; Rahma, S; Stubbs, N; Hinchcliff, R; Wright-Hughes, A; Nixon, J; Richards, S; Russell, D
Abstract: Introduction: This is the first clinical case series to report time to ulceration, minor and major amputation of the contralateral limb (CLL) in the first 12 months following major lower limb amputation (LLA) in patients with peripheral arterial disease (PAD) and/or diabetes. Method: Consecutive patient samples at two regional UK vascular centres were included; from 2010 to 2017 (site 1) and 2014 to 2016 (site 2). Data were extracted from electronic records for 12 months following index major LLA. Survival analyses are presented for the event of mortality in the total study population, plus major amputation-free survival, and complication-free survival in site 1 only; results are stratified by diabetes status. Results: Of 381 patients reviewed (n = 197 site 1; n = 184 site 2), 208 (54.6%) were diagnosed with diabetes at the time of their index major LLA. The mean survival time of patients was lower in those without diabetes (HR: 0.64 [95% CI, 0.43 to 0.95], p=.03). The mean time to major amputation of the CLL or death in patients was lower in those without diabetes (HR: 0.65 [95% CI, 224 0.40 to 1.06]; p=.08). The median time to any complication of the CLL or death was greater in those without diabetes (HR: 1.25 [95% CI, 227 0.88 to 1.78]; p=.21). Conclusions: Death rates were higher in patients without diabetes, whilst those with diabetes had high levels of CLL complications. Optimisation of care to protect the CLL following major LLA and guidance for carers, patients, and clinicians is required.